Pelatihan Baca Syair Siswa Kelas XI SMA Negri 2 Siak Hulu - Rahayu, Sri; Wahyuni, Reni; Hermaliza, Hermaliza; Afdal, Adristi; Raudhoturrahmah, Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
This training activity was carried out with the aim of providing training for grade XI students of SMA Negeri SIAK HULU on reading poetry. This community service uses a descriptive method, meaning it is descriptive in nature by describing what it is. The results of the community service activities on poetry reading training have achieved their targets well with details of the activities in the form of providing material to students about poetry then continued with discussions and questions and answers about the discussion followed by poetry reading practice activities, the activity ended with poetry reading practice. The most important thing is that the students have been able to understand poetry reading techniques and are able to practice reading poetry. The benefits that can be seen in terms of readiness in the form of high self-confidence possessed by students so that they are able to appear in front of the audience by paying attention to important aspects in reading poetry. Based on the community service activities, it was concluded that the activities went smoothly with the results that students were able to read poetry well.